UNIVERSITY ADMINISTRATION IN THE CONTEMPORARY CONDITIONS - R. G. Strongin (Высшее образование в России, 2017)
At present time, many of the Russian foremost higher educational institutions acquire some typical features of the third generation universities [1]. Their indispensable adaptation to the new conditions gives rise to some significant transformations of own structure. The need to develop forestall education for promoters of fast emerging multidisciplinary technologies leads to melting and separating the university divisions and also to establishing interdepartmental teams. The universities serve as centers of network interaction with partners and business enterprises. Intensive interpenetration of project and administrative management forms becomes typical. Arising therefore painful changes in the roles of particular teams and their key members are to be alleviated due to proper management style. The influence of such collectively adopted documents as the university Mission and Strategy increases significantly. The paper dwells on the specific characteristics of arising management problems closely connected with the development ofmultidisciplinary forestall education in the area of biomedicine and biotechnologies at the Nizhni Novgorod Lobachevsky State University. The author stresses that at the contemporary stage the university acquires the features of an open system (in Prigogine's interpretation).